Next Generation Sequencing for a Plant of Great Tradition: Application of NGS to SNP Detection and Validation in Hops (Humulus lupulus L.). - Hop Special - Matthews, Paul D.; Coles, Marc C.; Pitra, Nicholi J. (BrewingScience, 2013)
Application of next generation DNA sequencing technology to hops yielded an unprecedented, large number of novel single nucleotide polymorphisms (17, 128 SNPs). The markers were detected and then validated for use in genotyping and control of quality for hops. By using genotyping-by-sequencing (GBS) and a universal network-enabled analysis kit (UNEAK) designed for species with no "reference genome", we generated a set of molecular markers with a genome-wide distribution. Validation of the markers was accomplished by observation of metrics of sequencing quality, by marker behavior in genetic segregation and by application to genetic distance and hierarchical cluster analyses across a set of commonly known cultivars. The SNPs were characterized by average read depth of 3.7 and a call rate across 178 diverse individuals of 0.82. Many SNP alleles segregated with near test cross ratios of 1 : 3 or 3 : 1 and intercross ratios of 0.50 among 103 full-siblings. Erroneous SNPs, with unusually high or low allele segregation ratios were detected at a rate of 4.1 % and could be removed from further analyses. Filtering of SNPs for potentially higher quality was accomplished by selection of call rate thresholds above 0.5, 0.75 and 0.90 or, alternatively, by selection of markers with minimal segregation distortion. Genetic distance matrices and dendrograms for marker subgroups were similar as shown by Mantel?s Z-tests and cophenetic correlation coefficients. Bootstrapping generated an exceptionally well-supported tree for genetic relationships among the hop cultivars.